THE INFLUENCE OF JOB CONFLICT AND JOB STRESS ON ORGANIZATIONAL COMMITMENT WITH ORGANIZATION CITIZENSHIP BEHAVIOR AS AN INTERVENING VARIABLE IN THE MEDAN RELIGIOUS TRAINING CENTER - Sejahtera, Toto; Farida Ferine, Kiki (Penerbit Lafadz Jaya, 2023)
The purpose of this study was to determine the Effect of Work Conflict and Work Stress on Organizational Commitment with Organizational Citizenship Behavior as an intervening variable. The type of research used was associative quantitative research locations at the Medan Religious Education and Training Center. the results of this study are. Work Conflict has no significant negative effect on Organizational Commitment. Work conflict has a positive and significant effect on OCB. OCB has a positive and significant effect on Organizational Commitment. Work Stress has a negative and insignificant effect on Organizational Commitment. Work Stress has a positive and significant effect on OCB. Work Conflict has a positive and significant effect on Organizational Commitment through OCB. Work Stress has a positive and significant effect on Organizational Commitment through OCB.